The Evolution and design of Hastilinga Crematorium in Northeast, Thailand - Wongpongkham, Niyom; Sriruksa, Kittisan (Journal of Fine and Applied Arts Khon Kaen University, 2022)
The study of the Evolution and design of Hastilinga crematorium in Northeast Thailand was qualitative research. The process of research is started from data collecting. Fieldwork surveying and interview, then classification, grouping and analysis were done in order to characteristic summary. The result of this research can be develop in related field of discipline. The result found that the evolution and design of Hastilinga crematorium Northeast, Thailand has keep on the traditional style, not only in construction technique but conceptual design, base on traditional is developed continually. There are 3 groups of forming design: 1) Busabok with glass pavilion in spiral roof, 2) Hastilinga crematorium with in crown shaped roof and four pillars structure, and 3) Busabok crown shaped roof and four pillars structure on the ground.